Prevalence of psychiatric disturbances among school going children in North Karnataka - Archana Basavaraj Byahatti; Azizahmed I Arbar; Rohit Rajendra Natekar; Sindhu N Reddy; Ghansham Jadhav (Wolters Kluwer Medknow Publications, 2021)
Context: Psychic Disturbances are the most common problems encountered in children. Aims: To study the prevalence of Psychic Disturbances like anxiety and depression among high school going adolescents. Settings and Design: This is cross-sectional survey study conducted among 522 children (13-15 years). Methods and Material: Anxiety and Depression were measured using Hamilton anxiety rating scale and Kutcher adolescent depression scale respectively. Statistical analysis used: The collected data were analyzed using Statistical Package for Social Science(SPSS statistics 20 License Authorization Wizard.Ink).Results were expressed as proportions using appropriate tables. Prevalence rate was calculated using point prevalence formula. Results: The response rate of study being 91.7%, Among total samples of 522, 403 samples (77.2%) had only mild anxiety,14.17 % participants had possible depression another 14.17 % of participants having both anxiety and depression. Conclusions: Prevalence of Anxiety was higher compared to Depression among the study participants, females had higher prevalence rate of depression were as males had higher rate of anxiety.